A CMOS variable gain LNA for UWB receivers - 谌斐华 李凌云 多新中 田彤 孙晓玮 (Journal of semiconductors, 2011)
A CMOS variable gain low noise amplifier （LNA） is presented for 4.24.8 GHz ultra-wideband appli- cation in accordance with Chinese standard. The design method for the wideband input matching is presented and the low noise performance of the LNA is illustrated. A three-bit digital programmable gain control circuit is exploited to achieve variable gain. The design was implemented in 0.13μm RF CMOS process, and the die occupies an area of 0.9 mm2 with ESD pads. Totally the circuit draws 18 mA DC current from 1.2 V DC supply, the LNA exhibits minimum noise figure of 2.3 dB, S（1, 1） less than -9 dB and S（2, 2） less than -10 dB. The maximum and the minimum power gains are 28.5 dB and 16 dB respectively. The tuning step of the gain is about 4 dB with four steps in all. Also the input 1 dB compression point is -10 dBm and input third order intercept point （IIP3） is -2 dBm.